2015
DOI: 10.1098/rstb.2014.0112
|View full text |Cite
|
Sign up to set email alerts
|

Competing pressures on populations: long-term dynamics of food availability, food quality, disease, stress and animal abundance

Abstract: Despite strong links between sociality and fitness that ultimately affect the size of animal populations, the particular social and ecological factors that lead to endangerment are not well understood. Here, we synthesize approximately 25 years of data and present new analyses that highlight dynamics in forest composition, food availability, the nutritional quality of food, disease, physiological stress and population size of endangered folivorous red colobus monkeys ( Procolobus rufomitratus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 99 publications
0
41
1
2
Order By: Relevance
“…Variation in survival is relatively straightforward to determine, provided individuals can be recognized and followed, but survival estimates are generally complicated by dispersal, and causes of mortality must be separated into those due to extrinsic causes (primarily predation) and those attributable to infection and non-infectious diseases. For example, Chapman et al [116] use demographic data collected over decades to make inferences about the effects of stress and new parasites on population dynamics in red colobus monkeys, and recent studies revealed that survival is affected by social relationships in female baboons [117] and male bottlenose dolphins [118].…”
Section: (D) Fitness Consequencesmentioning
confidence: 99%
“…Variation in survival is relatively straightforward to determine, provided individuals can be recognized and followed, but survival estimates are generally complicated by dispersal, and causes of mortality must be separated into those due to extrinsic causes (primarily predation) and those attributable to infection and non-infectious diseases. For example, Chapman et al [116] use demographic data collected over decades to make inferences about the effects of stress and new parasites on population dynamics in red colobus monkeys, and recent studies revealed that survival is affected by social relationships in female baboons [117] and male bottlenose dolphins [118].…”
Section: (D) Fitness Consequencesmentioning
confidence: 99%
“…With limited area available for movement and foraging, primates turn to anthropogenic food sources, such as provisioned feeding spots or crop raiding, to survive within a highly humanized environment (Hoffman and O'Riain 2012). Food availability has been shown to be a key factor contributing to group dynamics, most notably population size and structure, as well as aggressive interactions among conspecifics (Chapman et al 2015;Oro et al 2004). As food provisioning in the urban habitat provides a constant source of nutrition, this can have a considerable impact on population ecology (Altmann and Muruthi 1988;Hill 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Links between health, sociality and fitness also have important implications for conservation biology, as highlighted by the contribution to this theme issue by Chapman et al [10]. Conservation biologists often consider the problems that arise in small populations, which of course is characteristic of endangered species.…”
Section: (F ) Implications For Conservation Biologymentioning
confidence: 99%
“…A final example of surprising results comes from Chapman et al's [10] contribution to the theme issue. In this paper, the authors investigated a series of predicted links involving food quality and availability, glucocorticoid levels as a marker of stress, and abundance of wild red colobus monkeys.…”
Section: (B) Exceptionsmentioning
confidence: 99%
See 1 more Smart Citation